The Effect Of The Lorsbach Model On The Acquisition Of Concepts And Attitudes Towards Aesthetics Among Students Of The Department Of Art EducationNumbers (Journal of the College of Basic Education, 2025)
The current research seeks to identify the effect of the Lorsbach model on the acquisition of concepts and attitudes towards aesthetics among students of the Department of Art Education. In order to achieve the objectives of the current research, the researcher followed the steps of the quasi-experimental approach through two experimental and control groups amounting to (86) divided equally between both groups. The third grade in the Department of Art Education and the two branches (A) and (B) were chosen to be the research sample. The researcher built a test to measure concepts in aesthetics as well as a scale of attitudes towards the subject and verified the psychometric properties. After applying the experiment, the study reached the following results:The Lorsbach model had an effect on the acquisition of concepts in aesthetics by students of the experimental groupThe Lorsbach model achieves positive attitudes towards aesthetics for students of the experimental group compared to the control group.